4,6-Diaryl-5,5-difluoro-1,3-dioxanes as chiral dopants for liquid crystal compositions - Maurice Médebielle; Peer Kirsch; Jérémy Merad; Carolina von Essen; Clemens Kühn; Andreas Ruhl (Beilstein Journal of Organic Chemistry)
Two racemic anti-4,6-diphenyl-5,5-difluoro-1,3-dioxanes were prepared and the corresponding enantiomers were evaluated as potential new chiral dopants for liquid-crystal compositions.